PTU-114 Expression of toll-like receptor (TLR)-2 and -4 in the intestinal crypt epithelial cells in inflammatory bowel disease (IBD). (28th May 2012) - Brown, M R L; Robins, A; Mahida, Y R
Abstract : Introduction: TLRs are pattern recognition receptors which detect conserved molecular patterns on commensal and pathogenic bacteria. Studies in mice have shown that TLR signalling protects against the development of colitis but may exacerbate established colitis. Epithelial stem cells and their progeny are located in crypts of the small and large intestine. We have investigated TLR2 and TLR4 expression in ulcerative colitis (UC) and Crohn's disease (CD) crypt intestinal epithelial cells (IEC). Methods: Ileal and colonic mucosal samples were obtained from operation resection specimens and were histologically normal (>5 cm from cancer; normal controls) or inflamed (CD or UC). Additionally, paired samples from histologically normal (proximal colon) and inflamed (distal colon) mucosa were obtained from five colectomy specimens with isolated left-sided UC. Crypt IECs were isolated using EDTA and pancreatin. Expression of mRNA transcripts was studied by conventional and real-time RT-PCR. Cell surface TLR protein was studied by flow cytometry (expressed as median fluorescent intensity, MFI). TLR expression was also studied by immunofluorescent (IF) staining of tissue sections. Data are expressed as median (IQR). Results: Relative to normal controls, TLR2 mRNA expression in IEC was significantly elevated in inflamed colonic UC [3.18-fold (1.03–10.40), p=0.003] and inflamed colonic CD [3.45 (0.80–5.40), p=0.012]. TLR4 mRNA was significantly elevated in normal colonic UC [1.90 (1.69–4.31], p=0.017), inflamed colonic UC [2.33 (1.15–4.45), p=0.024], inflamed colonic CD [1.71 (1.00–4.32), p=0.042] and inflamed ileal CD [1.84 (1.43–4.66), p=0.03]. In paired analyses, IEC TLR2 and TLR4 mRNA expression was not significantly different in normal UC mucosa compared to inflamed UC mucosa. Compared to IEC from normal control colon, IEC from colonic CD showed significantly greater expression of cell surface TLR2 protein [MFI 10.1 (2.4–29.0) vs 33.1 (17.7–107.5), p=0.05] and TLR4 protein [MFI 12.1 (4.9–25.3) vs 40.9 (23.2–103.5), p=0.04]. IF staining confirmed TLR2 and TLR4 protein expression on the luminal surface of crypt IEC. Conclusion: IEC expression of TLR4 mRNA was up-regulated in inflamed and un-inflamed colonic and ileal IBD. TLR2 mRNA was up-regulated in inflamed colonic IBD. Interestingly, TLR2 and TLR4 mRNA expression was similar in IECs isolated from un-inflamed, histologically normal mucosa as it was in IECs isolated from inflamed mucosa in UC. This may suggest TLR2 and TLR4 up-regulation is a primary rather than secondary event in UC. Moreover, TLR2 and TLR4 protein was expressed in greater amounts on the surface of IECs in CD. Competing interests: None declared.